Season‐specific varietal management as an option to increase rainfed lowland rice production in East African high altitude cropping systems - Abera, B.B.; Stuerz, S.; Senthilkumar, Kalimuthu; Cotter, M.; Rajaona, A.; Asch, F. (Wiley, 2020)
Due to land expansion and an increase in productivity, rice production in sub‐Saharan Africa has been growing at a rate of 6% in the past decade. Rainfed rice production systems have accounted for a large share of this expansion. In these systems, the potential growing period not only depends on the length of the rainy season and thus water availability, but is often, especially in the highlands of East Africa, bordered by the onset of the cool period of the year, when low minimum temperatures compromise rice yields. The objective of this study was to investigate the yield potential of 30 rice varieties contrasting in crop duration and cold tolerance in the highlands of East Africa, with its limited length of growing period. A field trial was conducted in the cropping seasons in 2016 and 2017 at the Fogera rice research station, Ethiopia. As a function of the onset of rains, rice was sown mid‐July in 2016 and early July in 2017. Early sowing in 2017 led to an extended crop duration and significantly lower yields of the short‐duration varieties, and to a shortened duration and significantly higher yields of the medium‐ and long‐duration varieties, when compared to late sowing in 2016. Late sowing compromised yield of the medium‐ and long‐duration varieties because of low temperatures during booting stage, which led to high spikelet sterility. Early sowing resulted in low yields of the short‐duration varieties, probably due to low solar radiation during the cloudy rainy season, which coincided with the vegetative stage. Therefore, choice of variety should be a function of the variable onset of the rainy season and related sowing date. However, crop models precisely calibrated for potential varieties and the respective environmental conditions could fully support the selection of a suitable variety, depending on the date of sowing, for example with the help of online tools or smartphone applications.